2017
DOI: 10.1016/j.vaccine.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

A randomized Phase III clinical trial to assess the efficacy of a bovine-human reassortant pentavalent rotavirus vaccine in Indian infants

Abstract: HighlightsPentavalent reassortant rotavirus vaccine was tested for efficacy in infants.The vaccine (BRV-PV) showed excellent tolerability and a good safety profile.Primary analysis efficacy was 36% against SRVGE and up to 60.5% against VSRVGE.The efficacy through 2 years of age was 39.5% (SRVGE) and 54.7% (VSRVGE).The intent to treat analyses confirmed all the per protocol analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 34 publications
5
104
0
1
Order By: Relevance
“…For the last many years, vaccines against diphtheria, pertussis, tetanus, hepatitis B, haemophilus influenzae type b, and polio have also been given at these time points. As per regulatory requirements, it has to be demonstrated that any new vaccine does not interfere with the immune responses to these vaccines [7] .…”
Section: Introductionmentioning
confidence: 99%
“…For the last many years, vaccines against diphtheria, pertussis, tetanus, hepatitis B, haemophilus influenzae type b, and polio have also been given at these time points. As per regulatory requirements, it has to be demonstrated that any new vaccine does not interfere with the immune responses to these vaccines [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the VP4 and VP7 reassortants generated here may be useful for the generation of vaccines based on strains circulating in Africa. Recently, two additional rotavirus vaccines (Rotavac and Rotasiil) have been developed in India [55,56]. Rotavac is based on strain 116E, which is a naturally-occurring G9P [11] human reassortant with bovine VP4 and was originally isolated from neonates with asymptomatic infection in India [57].…”
Section: Discussionmentioning
confidence: 99%
“…ROTASIIL, developed by the Serum Institute of India, is a bovine/human reassortant vaccine. It comprises the G6P [5] bovine rotavirus as a backbone, with the VP7 genes from human rotavirus strains incorporated to produce reassortant strains [10]. The vaccine received national licensure in India by the DCGI in 2016, and is awaiting WHO prequalification.…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%